Fabrication and Electrical Characterization of Translucent Bi12TiO20 Ceramics - D. J. Santos; L. B. Barbosa; R. S. Silva; Z. S. Macedo (Advances in Condensed Matter Physics)
The production of high-density Bi12TiO20 ceramics, their transmission spectrum, and impedance features are reported. The samples were synthesized at 700°C/6 h and sintered at 800°C/3 h. This procedure yielded translucent ceramics with relative density of 99.2±0.5% and average grain size of 3.1±1.6 μm. Samples with 0.5 mm thickness were translucent with optical transmission of about 30% at 800 nm. The electrical and dielectric properties of the high-density ceramics were studied and compared with those measured for samples with lower density and also with the literature about Bi12TiO20 single crystals. The activation energy for the conduction process in high-density ceramic was 0.99 eV, and the dielectric permittivity was 40 at 200°C. These values are comparable to those reported for single crystals.